THE CARCINOGEN EFFECTS OF DIMETHYLAMINOAZOBENZEN (DMAB) DYE ON THE SKIN OF RATS - MAJEED. H. MAJEEDIAL-SARRY (Basrah Journal of Veterinary Research)
The effects of dimethylaminoazobenzene dye were studied in rats by exposing skin directly to the dye. Twenty one mature rats Rattus norvegicus were divided into three groups and I represented by (control group Tlgroup treated with ether (vehicle) only, and T2 group treated with dimethylaminoazobenzene. dissolved in ether). The obtained results concluded the carcinogenic effects of dimethylaminoazobenzene depending on marked grossly and histological changes represented by appearance of skin cancer (squamous cell carcinoma and basal cell carcinoma) types in T2 group